Global Climate Change Impacts on Local Climate and Hydrology - Breuer, Lutz; Exbrayat, Jean Francois; Plesca, Ina; Buytaert, Wouter; Ehmann, Theresa; Peters, Thorsten; Timbe, Edison; Trachte, Katja; Windhorst, David (Ecosystem services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador. Ecological Studies, 2013)
Global climate change will most likely have a severe impact on local climate and hydrological cycling in the tropical montane rainforest. We used a simple statistical downscaling technique for eight general circulation models and two IPCC AR4 emission scenarios (A1B, A2) to forecast feasible local climate conditions for the San Francisco river basin for three future time slices (2010–2039, 2040–2069, 2070–2099). These simulations were then used as forcing data for an ensemble of seven catchment scale rainfall-runoff models to investigate the effects on local hydrological fluxes. Precipitation for both emission scenarios is expected to increase, especially in the months May and June. These increases in precipitation input will lead to even more dynamic discharges as today. However, part of the increasing water input is compensated by raising evapotranspiration due to higher temperatures. Finally, we give an outlook on feasible future trends of water-related ecosystem services under climate change.
UnivIS-Import:2015-04-20:Pub.2012.nat.dgeo.IG.zentr.global